Effectiveness of Raltegravir in Combination with Atazanavir/Ritonavir and Lamivudine as Secondline ART- a Case Report - Dr. Sri Rama B Rao (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Increase in the number of people being initiated on Anti retroviral therapy, there is inevitably an increase in the number of people failing first-line therapy. The choice and rationale for selection of second-line therapy is limited. Constructing a second line regimen is a challenge for patients who have been exposed to all classes of NRTI’s in resource poor settings. The combination of Raltegravir with boosted atazanavir is a viable option if proved effective in trials with sufficient statistical power. We report a case of 48 week follow-up data of a patient started on Boosted atazanavir with Lamivudine and Raltegravir as secondline.